Assessing the employment and social impacts of selected strategic Commission policies : final report (Rotterdam, 2009)
"Identification and assessment of employment and social impacts are challenging exercises due to their diversity and complexity. Proposed policy options may create and/or destroy jobs, affect people's incomes and quality of life, support their participation in society, etc.